Analisis Dampak Kebijakan Pemerintah dan Determinan Impor Kedelai Indonesia 1983‒2019 - Ardhana, Fadhil Mukti; Sa'adah, Miftahus; Putri, Nabila Yahya; Sedana Nugraha, I Gusti Ngurah Yogi; Pambudi, Thessa Fauziah; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
Soybean is a primary commodity in Indonesia with a large dependence on imports, this shows the magnitude of the challenge in realizing soybean self-sufficiency which might cause problems later. This study aims to determine the development of soybean production, consumption, and import patterns along with factors that influenced soybean imports in Indonesia in the period 1983 to 2019. Simulations were also carried out with changes in values of several variables to determine resulting impact on soybean imports. Analysis was performed using simultaneous equations with the Two Stage Least Square (2SLS) method. The results showed that the pattern of development of soybean consumption and imports from 1983 to 2019 tended to increase, but the decline occurred in soybean production. Based on the results of the 2SLS method, it is known that consumption has a positive effect on soybean imports while production has a negative effect. Conversely, production has a positive effect on soybean consumption, but is negatively affected by per capita GDP. It is also known that soybean production is positively influenced by harvested area and domestic soybean prices. The simulation results show an increase in soybean production and consumption will occur when domestic soybean prices are increased or restrictions on the volume of soybean imports in Indonesia are imposed.